Sajos - Konceptmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2026)
Sajos is a cultural center for the Sámi population of northern Finland in the cultural capital of Inari. It contains a multitude of functions: The Finnish Sámi Parliament, a children's cultural center, conference and event venues, a doudji (handicraft) shop, an educational institute, the Indigenous People's Film Centre, a library, a music center, a restaurant, the Sámi Archives, and spaces for local associations. The design of the building was decided through an open competition taking place in 2008. It was won by a young team of newly-graduated and still studying architecture students. Their design features a large open lobby with clear connections to the surrounding nature, light wooden walls inside, and rounded shapes inspired by the concepts found within traditional Sámi handicraft. Further reading: https://www.sajos.fi/, https://samediggi.fi/en/, https://alt-arkkitehdit.fi/en/projects/sami-cultural-center-sajos/, https://www.archdaily.com/228027/sami-cultural-center-sajos-halo-architects
Sajos - Concept model
Keywords: Sámi Architecture; Sámi Parliament; Samediggi; Cultural Center; Parliament; Sapmi; Finnish Architecture; Library; Archive; Event Venue; Auditorium